2016
DOI: 10.1186/s12879-016-2031-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and RAPD-PCR typing of thermophilic campylobacters from children under five years and chickens in Morogoro Municipality, Tanzania

Abstract: Background: Campylobacter species are gram negative and flagellated bacteria under the genus Campylobacter, family Campylobacteriaceae. These pathogens cause zoonotic infections among human and animal populations. This study was undertaken between December 2006 and May 2007 to determine prevalence, risk factors and genetic diversity of thermophilic Campylobacter isolates from children less than 5 years and chickens in Morogoro Municipality, Tanzania. Methods: The Skirrow's protocol was used for isolation and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
3
14
1
1
Order By: Relevance
“…Detection of genotypic relatedness among some C. coli and C. jejuni isolates recovered from aquatic milieu and meat sources confirmed that livestock and poultry are sources of environmental spread of Campylobacter species and these results is in accordance with the report of [ 54 ]. Genetic diversity is one of the different mechanisms that helps pathogens to thrive in unfriendly circumstances within the environment or in the host given them the ability to colonize multiple hosts [ 55 ]. Genomic rearrangement and horizontal gene transfer are among the diverse phenomena that can cause genetic diversity in C. jejuni and C. coli [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Detection of genotypic relatedness among some C. coli and C. jejuni isolates recovered from aquatic milieu and meat sources confirmed that livestock and poultry are sources of environmental spread of Campylobacter species and these results is in accordance with the report of [ 54 ]. Genetic diversity is one of the different mechanisms that helps pathogens to thrive in unfriendly circumstances within the environment or in the host given them the ability to colonize multiple hosts [ 55 ]. Genomic rearrangement and horizontal gene transfer are among the diverse phenomena that can cause genetic diversity in C. jejuni and C. coli [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies found a prevalence lower than 30%. A Ghanaian study found Campylobacter in 22.5% of ceacal samples [37], a Tanzanian study in 42.5% of chickens (various breeds) using cloalcal swabs [12] and an Ethiopian study, in 28.9% of chickens (various breeds) [45]. A study from 1988 found a prevalence of 51.5% in Kenyan broilers [46], whereas a 2018 study found an overall prevalence of 69.5% in Nairobi chickens [28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in Ethiopia and Tanzania have identified marked differences in prevalence between broiler and indigenous chicken flocks, with conflicting results. Two studies in Tanzania found a higher Campylobacter prevalence in indigenous chickens (76.49% and 75%) compared to broilers (26.4% and 50%) [47,12]. Another Tanzanian study found no significant difference between broilers and indigenous chickens, but rather a higher prevalence in local chickens from rural areas compared to those in urban areas [48], while an Ethiopian study found significantly higher Campylobacter isolation rates in animals (chicken, sheep, cattle and pigs) in urban areas (56.7%) compared to rural areas (26.7%)[49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 33 articles, only four reported on risk factors of campylobacteriosis in humans. In Tanzania, Campylobacter infections were associated with sex, young age, poultry meat consumption, and eating of salads [26,38]. In Ethiopia, human campylobacteriosis was significantly associated with nonuse of latrines, water source, drinking unboiled water, bottle feeding, nutritional status, and exposure to domestic animals including cats, dogs, poultry, and pigeons [25].…”
Section: Campylobacter Infections In Humansmentioning
confidence: 99%